Produktion - Distribution - Ökonomie. Siedlungs- und Wirtschaftsmuster der Latènezeit - Mölders, Doreen (H-Net Reviews in the Humanities & Social Sciences, 2011)
The article reports on a conference on the economic history of the Latène period of the European Iron Age, held in Otzenhausen, Germany, from November 28-30, 2011. Topics discussed included theories of economy and society during this era, particularly that of Austrian economist Karl Polanyi, economic archaeology research, and the trade networks of traditional societies.
Keywords: Europe; LA Tene period; POLANYI, Karl, 1886-1964; TO 500; archaeology research; commerce; congresses; economic history; history; iron age; traditional societies

Embedding Markets in Temporal Structures: A Challenge to Economic Sociology and History - Eisenberg, Christiane (Die Einbettung von Märkten in temporalen Strukturen: Eine Herausforderung für Wirtschaftssoziologie und Geschichte., 2011)
The essay examines from a historian's point of view the approaches to the analysis of market exchange in new economic sociology and explores in which way sociology and history can cooperate in embedding markets in temporal structures. In a first step the author sharply criticises the favourable reception given to Karl Polanyi's work "The Great Transformation" in the field of new economic sociology. In particular she discusses the narrowing of research perspectives and its negative side effects on the sociology of markets. There then follows a second step: in order to find a linking point for interdisciplinary cooperation, beginning with the current state of historical research, the author makes several considerations on the significance of temporal structures and the time factor in general in analysing markets and market societies.
Keywords: Continental Europe; England; Great Britain; economic history; economic sociology; history - methodology; interdisciplinary approach to knowledge; interdisciplinary research; longue durée; market society; socioeconomics; time structures

Karl Polanyi's Institutional Theory: Market Society and Its "Disembedded" Economy - Cangiani, Michele (Journal of Economic Issues, 2011)
A fundamental principle of Karl Polanyi's institutional outlook is that any economic system has to be considered as a whole and as a historically specific social organization. This principle implies a comparative method and a critique of conventional economics. Besides, the problem of the interrelation between the economic system and other aspects of social life cannot be avoided. On this basis, Polanyi points out the peculiar "economic" nature of the market-capitalist society and explains the institutional transformations characterizing its history. The opposition "embedded/disembedded," used by Polanyi to distinguish pre-modern economies from the market economy, has been widely adopted in recent times, particularly by economic sociologists, as a key for understanding current complex economic phenomena. However, the reference to Polanyi often presupposes a distorted interpretation of his theory, and a different kind of institutional approach.
Keywords: comparative economics; disembedded economy; economic policy; economic systems; embedded economy; institutional economics; institutional method

À propos de « ceux qui sont en dehors de la société ». L'indigent et l'assistance publique au Québec dans la première moitié du XXe siècle - Petitclerc, Martin (Revue d'histoire de L'Amerique francaise. automne2011/hiver2012, Vol. 65 Issue 2/3, p227-256. 30p., 2011)
The “ Loi établissant le service de l'assistance publique" (Public Welfare Act) sparked considerable controversy after its adoption in 1921 .The Act provided for provincial and municipal grants to private and religious institutions providing shelter to the poor and destitute. Led by Henri Bourassa, among others, the debate concerned the problem of state intervention in an area traditionally conceived of as the responsibility of the Church. In contradiction to Bourassa's theories, most historians analyzed the A c t through the rubric o f modernization as a necessary affirmation of State prerogatives in the area of social protection. In this article, we argue that this Act is an attempt (largely successful) to consolidate a form of liberal governmentality based on, since the 19th century, what Karl Polanyi termed “the figure of the pauper" According to this perspective, the 1921 A c t is not a significant stage in the age-old struggle between Church and State, but rather a time of reform in liberal politics in regards to "the indigent 'The latter leggally defined as unable to work and without family support, and therefore “ outside of society," an expression of the day, allowed justifying the development o f a private/public system of charitable assistance against the project o f social policies founded on a universal conception of social rights. The article presents this dynamic through an analysis of the contentious issue of the rights of indigents to public assistance. (English)
Keywords: BOURASSA, Henri, 1868-1952; Canada; Quebec; church & state - Canada; liberalism - Canada; poor people - Canada; poor people - government policy; poor people - services for - history; public welfare - Canada - history